MAKNA SIMBOLIK PANTUN DALAM TRADISI MULANG-MULANGKAN PADA MASYARAKAT MELAYU SAMBAS - Sulissusiawan, Ahadi (LITERA, 2015)
Abstract This study aims to describe symbolic meanings of pantun in the mulang-mulangkan tradition in the Sambas Malay community. The mulang-mulangkan tradition is a Malay tradition through which the parents of the bride and groom hand over the couple to families and relatives to be well accepted. The study employed the ethnographic approach by applying the analysis according to the ethnographic framework by Spradley. The analysis was conducted by investigating symbols based on the contexts and relational meanings of folk terms in pantun in relation to the cultural life of the community possessing the text. The results of the data analysis show that the folk terms in the Sambas Malay community contain symbolic meanings. Some of them are advice on a pure bride, advice on bitterness in family life, advice on loyalty and willingness to sacrifice, advice on patience and trust in God to face life, advice on problem solving through agreement, advice on diligence in saying prayers and not being lazy in family life, and advice on inviting others when a baby is born.